Comparison of Customer Complaint Management in Conventional and Sharia Financial Institutions: A Review Based on the Principles of An-Taradin - Bahari Alfalah; Hafidza Sanshia Arum (JAWI : Journal of Ahkam Wa Iqtishad, 2026)
Customer complaint management is an important aspect in maintaining customer satisfaction and loyalty to financial institutions. This study aims to analyze the comparison of customer complaint management in conventional and sharia financial institutions based on the principle of an-taradin. The research uses the library research method  with a descriptive-comparative approach through the analysis of various literature, scientific journals, books, regulations, and relevant documents. The results of the study show that conventional and sharia financial institutions have the same goal in resolving customer complaints, but differ in their orientation and approach to resolution. Conventional financial institutions focus more on customer satisfaction and service effectiveness, while Islamic financial institutions emphasize customer satisfaction as well as compliance with sharia principles, fairness, transparency, and benefits. Based on the principle of an-taradin, complaint settlement in Islamic financial institutions has a higher level of conformity because it places the willingness of both parties, the balance of rights and obligations, and voluntary acceptance of settlement results as an important part of the complaint handling process. This research also proposes a conceptual model of complaint management based on an-taradin that emphasizes transparency, deliberation, fairness, and willingness as the main elements in creating sustainable complaint resolution.